Scientific Investigation of Contemporary Pastel Painting by Roberto Sebastian Matta: Characterization of Original Materials through Multispectral Imaging and Spectroscopic Techniques - Colantonio, Claudia; Pelosi, Claudia; Calabrò, Giuseppe; Spizzichino, Valeria; Partenzi, Ilaria; Lanteri, Luca (Heritage, 2023)
The conservation of contemporary art often offers unique occasions to study complex multi-material artworks and understand their creative process and esteem degradation distress. The recent diagnostic campaign on the surrealist artwork Perché le vittime vincano (For the victims to win) (1974–75) by the artist Roberto Sebastian Matta allowed us to characterize the original painting materials (pastels on spolvero paper), never investigated and completely unknown, in order to support the imminent restoration. Due to the great dimensions of the artwork and its conservative issues, non-invasive multispectral imaging (HMI) analyses were done to investigate the whole painted surface, mapping and differentiating original materials and possible degradation patterns. Imaging data supported analytical characterization analyses run through elemental (portable X-ray fluorescence spectroscopy and scanning electron microscopy coupled with energy-dispersive spectroscopy) and molecular spectroscopy (Fourier transform infrared and portable µ-Raman spectroscopy) to identify the original artist’s materials and to support the restoration operations. The analysis revealed that the painting materials used by Matta are pastels characterized by modern pigments and dyes, such as Cu-phthalocyanines, chrome orange, titanium and zinc whites, compacted with kaolin without any organic binder or with a possible minuscule amount of gum.